18c-4-2c+12=

Simple and best practice solution for 18c-4-2c+12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18c-4-2c+12= equation:


Simplifying
18c + -4 + -2c + 12 = 0

Reorder the terms:
-4 + 12 + 18c + -2c = 0

Combine like terms: -4 + 12 = 8
8 + 18c + -2c = 0

Combine like terms: 18c + -2c = 16c
8 + 16c = 0

Solving
8 + 16c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 16c = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 16c = 0 + -8
16c = 0 + -8

Combine like terms: 0 + -8 = -8
16c = -8

Divide each side by '16'.
c = -0.5

Simplifying
c = -0.5

See similar equations:

| 54=x+5x | | 8u-6u=6 | | 5[x-3]=4[x+2] | | 11=4+v | | 12p+6=8p+30 | | 9x-30=2x+5 | | 47+11x=-30 | | (4x+3)=25 | | 179=6-u | | X-5.67=8.2 | | 12+x=3(3-2x) | | 47+11x=30 | | x(2x+1)=5x+1 | | 4[2-x]=5[x-2] | | -6u=4 | | 6(n-4)-(3-5n)=10n | | 5x=3-2y | | 8*x^3-6*x-1=0 | | 47+11=30 | | 3-1x=1 | | 3(8n-2)+8=(5+2n)-38+8n | | 3x+4+2x+1=6x-7 | | 10*x*100=50 | | 236=118-x | | 10*x=50 | | 11X-225=2X-9 | | -56=7g | | 4x-20=3x+6 | | x^5+i=0 | | 2(x+3)-6x-4=8+x | | is=3x+28 | | 0=x^2-1.998x+0.998 |

Equations solver categories